The distribution of profilin in root-tip cells of wheat seedlings exposed to enhanced UV-B radiation. Issue 1 (2nd January 2016) - Liu, Jiayu; Tie, Hailong; Chen, Huize; Han, Rong
ABSTRACT: Actin filaments play a significant role in regulating the cell cycle. The dynamic rearrangement of actin filaments are regulated by actin-binding proteins profilin (PFN). However, the distribution of PFN in root-tip cells and the role of PFN in the UV response have been unknown. Here, we observed the distribution of PFN during every stage of wheat cell mitosis in the control and UV-B treatment group, and found that PFN showed a punctuate pattern of localization around the periphery of nuclear envelopes in interphase and gathered toward the cell bipolar in prophase in the control treatment group. During metaphase, PFN presented a cage shape that is formed around the chromosomes, then appeared in the equator during anaphase, and re-distributed around the periphery of nuclear envelopes during cytokinesis. But PFN localization had changed under enhanced UV-B radiation (10.08 kJm –2 h –1 ), PFN displayed an annular distribution in interphase and, during metaphase, relatively large number of PFN distributed in one of the four corners or gathered in the four corners in the cell. However, two corners of PFN moved to the other two corners along the direction perpendicular to the cell-elongating axis during telophase. And these aberrant distributions of PFN were often associated with abnormal chromosome distribution.